The Property Rights Regulation, Semenda Marriage, and Exploring the Determinants in ASEAN Countries - Asrizal Saiin; Kholidah Kholidah; Zulfahmi Zulfahmi; Anwar M. Radiamoda; Kemas Muhammad Gemilang (Lembaga Contrarius Indonesia, 2023)
This study discusses the rights and position of the husband against his wife in the practice of semenda-marriage which is still in going today. This issue is discussed under the marriage law. Because this research is classified as qualitative research, the method used is normative juridical with descriptive analytical research. The analysis used in this research is critical discourse analysis. From the results of the study conducted, it was found that based on the theory of the rights and obligations of husband and wife in the family, that semenda-marriage are not in accordance with Indonesian marriage laws, because they position the wife as more powerful and superior to the husband. The rights and obligations of husband and wife have been explained in the marriage law, that what is the husband's obligation is the wife's right and what is the wife's obligation is the husband's right, and this is a concept of equality and complementarity. Apart from that, in the household life of indigenous peoples, regulations related to property rights are regulated. The husband's property rights in a semenda-marriages in ASEAN countries are that the husband has ownership rights to the assets of the wife. After the marriage takes place, there is a special event in handing over assets from the wife's family to the husband and wife, so that the assets from the wife's family become the property and responsibility of the husband and wife to manage and take care of the assets that existed at that time.